Critical curtailment location of EBR FRP bonded RC beams using dimensional analysis and fuzzy logic expert system. (15th April 2017) - Hoque, N.; Jumaat, M.Z.; Shukri, A.A.
Abstract: Fibre reinforced polymers (FRP) has been widely applied to strengthen reinforced concrete (RC) beams due to its high strength and low weight. However, despite widespread use and various researches on FRP strengthening, the problem of premature failure is still a concern. The present work aims to contribute to the current research on preventing premature failure of FRP strengthened RC beams by presenting a method to determine the safe curtailment location for externally bonded (EBR) FRP. In order to achieve this goal a dimensional analysis is used in combination with a parametric study of EBR strengthened beam using already existing global energy-based (GEBA) fracture mechanics analysis and fuzzy analysis. The proposed method is checked against published experimental data and shows good agreement.